FRI0192 MORTALITY IN IGA VASCULITIS: A LONGITUDINAL POPULATION-BASED STUDY. (2nd June 2020) - Nossent, J.; Ognjenovic, M.; Raymond, W.; Keen, H.; Inderjeeth, C.; Preen, D.
Abstract : Background: There is sparse population-level data on outcome in patients with Immunoglobulin-A vasculitis (IgAV) and none from Australia Objectives: We compared long-term mortality for paediatric and adult IgAV patients with age- and gender-matched controls. Methods: Linked health data for pediatric (<20 years=473) and adult (20+ years, n=267) IgAV patients were obtained from state-wide hospital and deaths registries in Western Australia for the period 1980-2015. All-cause mortality rates (MR) (deaths/1000 person-years) were compared with controls using mortality rate ratios (MRR) and with the general population of Western Australia by standardised mortality rate ratios (SMRR) with Poisson derived 95% confidence intervals (CI). We used Kaplan-Meier survival estimates and multivariate Cox regression derived hazard ratios (HR) for time dependent analyses. Results: In pediatric patients (mean age 7.2 years, 60 % male) MRR was 1.27 (CI: 0.34-4.08, p=0.68) and SMRR was 2.31 (CI: 0.72-5.7, p=0.47) (Table 1 ) with a 20-year survival rate (>99%) similar to controls. Despite higher rates of renal failure (1.5% vs 0.2%, p=0.002) deaths in pediatric IgAV patients were mainly from unrelated causes. In adult IgAV patients (mean age 55.8 years, 48% males) MMR was 2.06 (CI 1.70-2.50, p<0.01) and SMRR 6.16 (3.04 -14.3, p<0.01) (Table) during a mean of 19.5 years follow-up with significantly reduced survival at five (72.7 vs. 89.7 %) and twenty years (45.2% vs. 65.6 %) (p<0.05). Renal disease (HR: 1.47, CI 1.04 - 2.06), the presence of any comorbidity (HR:1.30, CI 1.23 - 1.37) and male gender (HR:1.23; CI 1.04 - 1.47) were independent predictors of death. While cardiovascular events (34.2%) and malignancy (19.4%) were the most frequent causes of death, only death from infections (5.8 vs 1.8%, p=0.02) and renal disease (3.6 vs 1.8%, p=0.03) were more frequent in adult IgAV patients than controls. Mortality data for childhood and adult-onset IgAV patients and controls. Figures indicate mean (±SD), numbers (%) or rate/1000 patient months (95% CI) Conclusion: Compared to controls and general population, mortality risk was not increased in paediatric IgAV patients for at least 20 years following diagnosis despite a higher rate of end stage renal failure. However, in adult IgAV patients, all-cause mortality risk was six times higher than in the general population leading to significantly reduced five-year survival, especially for male patients with comorbidity including renal disease. Acknowledgments: The authors thank the Data Custodians of the Hospital Morbidity Data Collection (HMDC), Emergency Department Data Collection (EDDC), the Western Australian Cancer Registry (WACR), the State Registry of Births, Deaths and Marriages, the WA Electoral Commission, and the NCIS for use of the CODURF dataset, and the staff at Data Linkage Branch at the Western Australian Department of Health for their assistance in provision of data. This work was supported by an unrestricted grant from the Arthritis Foundation of Western Australia. Author WDR received a PhD Scholarship in Memory of John Donald Stewart from the Arthritis Foundation of Western Australia. Disclosure of Interests: Johannes ("Hans") Nossent Speakers bureau: Janssen, Milica Ognjenovic: None declared, warren raymond: None declared, Helen Keen Speakers bureau: Pfizer Austrlaia, Abbvie Australia, Charles Inderjeeth Consultant of: Linear Research Perth, David Preen: None declared